Nanomaterials for promoting axon regeneration after spinal cord injury: Mechanisms and prospects - Jia Liu; Zhendong Huang; Xiner Tan; Wei Du; Ziyang Wang; Xinru Zhou; Hao Pan; Lili Chen; Yiyuan Kang; Longquan Shao (Interdisciplinary Medicine)
Abstract The establishment of new functional connections through axon regeneration is essential for functional recovery following spinal cord injury (SCI). With the rapid advancement of nanotechnology, nanomaterial (NM)‐based therapies have emerged as promising approaches to promote axon regeneration after SCI. Specifically, NMs can limit the spread of damage, maintain homeostasis in the extracellular environment surrounding injured axons, and ultimately facilitate axon growth following SCI. In particular, NMs with enzyme‐like properties, such as cerium oxide and manganese dioxide, can clear reactive oxygen species in the damaged area, thereby promoting axon regeneration. Additionally, NMs with electromagnetic properties can promote and guide axon regeneration under the influence of magnetic or electric fields. Importantly, the biological mechanisms by which NMs promote axon regeneration are summarized and discussed to explore promising NM‐based strategies for achieving functional recovery after SCI. Together, elucidating the physicochemical properties of NMs and the biological basis for their promotion of axon regeneration after SCI can help fill the gaps in our understanding of how NMs can be used to treat SCI and further the clinical translation of NMs in the future.